Outcome evaluation of micro credit scheme saving and internal lending community intervention from people living with human immunodeficiency virus in Magu District - Iriya, Lucy C (Mzumbe University, 2026)
Thesis to be Submitted to Mzumbe University the School of Public Administration and Management of Mzumbe University in partial fulfillment of Requirements for the Award of Master of Science Degree in Health Monitoring and Evaluation.